Identification of a nuclear localization signal and importin beta members mediating NUAK1 nuclear import inhibited by oxidative stress. Issue 9 (15th May 2019) - Palma, Mario; Riffo, Elizabeth N.; Suganuma, Tamaki; Washburn, Michael P.; Workman, Jerry L.; Pincheira, Roxana; Castro, Ariel F.
Abstract: NUAK1 is a serine/threonine kinase member of the AMPK‐α family. NUAK1 regulates several processes in tumorigenesis; however, its regulation and molecular targets are still poorly understood. Bioinformatics analysis predicted that the majority of NUAK1 localizes in the nucleus. However, there are no studies about the regulation of NUAK1 subcellular distribution. Here, we analyzed NUAK1 localization in several human cell lines, mouse embryo fibroblasts, and normal mouse tissues. We found that NUAK1 is located in the nucleus and also in the cytoplasm. Through bioinformatics analysis and studies comparing subcellular localization of wild type and NUAK1 mutants, we identified a conserved bipartite nuclear localization signal at the N‐terminal domain of NUAK1. Based on mass spectrometry analysis, we found that NUAK1 interacts with importin‐β members including importin‐β1 (KPNB1), importin‐7 (IPO7), and importin‐9 (IPO9). We confirmed that importin‐β members are responsible for NUAK1 nuclear import through the inhibition of importin‐β by Importazole and the knockdown of either IPO7 or IPO9. In addition, we found that oxidative stress induces NUAK1 cytoplasmic accumulation, indicating that oxidative stress affects NUAK1 nuclear transport. Thus, our study is the first evidence of an active nuclear transport mechanism regulating NUAK1 subcellular localization. These data will lead to investigations of the molecular targets of NUAK1 according to its subcellular distribution, which could be new biomarkers or targets for cancer therapies. Abstract : We identified that NUAK1 has a bipartite nuclear localization signal required for its nuclear import. Importin‐beta family members interact with NUAK1 and are responsible for its localization in the nucleus. Interestingly, oxidative stress led to NUAK1 cytoplasmic accumulation, indicating that its subcellular localization is affected by a cellular context previously associated with NUAK1 function.